PERBEDAAN LEVEL ONGGOK DAN LAMA FERMENTASI TERHADAP FRAKSI SERAT SILASE DAUN UBI KAYU - Harahap, Anwar Efendi (Jurnal Peternakan Nusantara, 2022)
One alternative agricultural waste that can be used for ruminant feed, especially in the dry season, is cassava waste with of silage. This study aims to determine the quality of the fiber fraction contained in the silage of cassava leaves with the addition of different levels of cassava flour and fermentation. This research used a factorial completely randomized design (CRD) with two treatment factors. Factor A (added level of cassava waste consists 0%, 25% and 50%) and factor B (fermentation time consists 0, 14 and 28 days). The parameters measured were the composition of the fiber fraction including Neutral Detergent Fiber (%), Acid Detergent Fiber (%), Acid Detergent Lignin (%), hemicellulose and cellulose (%). The results of this study indicate that there is an interaction between the addition of cassava waste levels and different fermentation times on the content of the fiber fractions of NDF, ADF, ADL, Hemicellulose and Cellulose. It can be concluded that the addition of 25% cassava waste level and 28 days of fermentation time can improve the quality of cassava silage fiber fraction